The Link between Greenwashing, Environmental Corporate Social Responsibility and Corporate Financial Performance: A Comparative Study in the Oil and Gas Industry - Zhang, Miao (2022)
The environmental corporate social responsibility (ECSR) of oil and gas (O&G) businesses has gained much attention due to environmental pollution accidents by significant O&G companies, such as the Mexican oil disaster. These issues also reveal that some companies are trying to convince stakeholders that they are engaging in corporate social responsibility (CSR) by deliberately disclosing information or promising to mislead stakeholders. This behaviour is known as greenwashing. While some academics have researched the existence of greenwashing by O&G corporations, others have studied the relationship between corporate financial performance (CFP) and CSR in environmental issues for O&G companies. However, an extensive study on the relationship between greenwashing, ECSR and CFP is lacking. This study demonstrates why O&G business needs to concentrate on ECSR and lessen greenwashing in its corporate operations based on stakeholder and legitimacy theories.